2018
DOI: 10.1093/cid/ciy559
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis Complicating Sacral Pressure Ulcers: Whether or Not to Treat With Antibiotic Therapy

Abstract: The treatment of osteomyelitis in patients with stage IV sacral pressure ulcers is controversial. We conducted a systematic literature review and did not find evidence of benefit of antibacterial therapy in this setting without concomitant surgical debridement and wound coverage. Furthermore, many patients with chronically exposed bone do not have evidence of osteomyelitis when biopsied, and MRI may not accurately distinguish osteomyelitis from bone remodeling. The goal of therapy should be local wound care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…The consequences of HAPI range from skin redness to full skin and tissue loss, exposing tendons and bones . If a person's injury advances, they face the prospect of osteomyelitis and sepsis . Issues such as pain, immobility, lack of independence, wound exudate, and odour impact patient's self‐image and emotional state, influence a person's quality of life …”
Section: Introductionmentioning
confidence: 99%
“…The consequences of HAPI range from skin redness to full skin and tissue loss, exposing tendons and bones . If a person's injury advances, they face the prospect of osteomyelitis and sepsis . Issues such as pain, immobility, lack of independence, wound exudate, and odour impact patient's self‐image and emotional state, influence a person's quality of life …”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery bypass surgery complicated by deep sternal wound infection frequently involves osteomyelitis of the sternal bone [ 22 ]. Elderly and paraplegic patients are at higher risk of developing deep tissue pressure injuries (i.e., pressure ulcers) that are frequently complicated by osteomyelitis [ 23 , 24 ]. As confirmed by our findings of the limited inhibition effect of 1MIC antibiotic levels, the efficacy of the traditional intravenous and oral antibiotic administration is often limited in these conditions due to the relatively low antibiotic concentrations that can be attained at the infection site.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative cost for each patient is multiplied when coupled with a readmission rate of 40% per year among spinal cord injury patients [ 10 ]. Moreover, a recent review of sacral pressure ulcers concluded that there is often futility in treating with long courses of intravenous antibiotics unless debridement and wound closure are performed, casting doubt on our ability to ever cure these infections [ 11 ].…”
Section: Gun Violence Is An Infectious Diseases Issuementioning
confidence: 99%